Analisis Kemampuan Literasi Matematis Berbasis Konteks Keislaman pada Mahasiswa Program Studi PGMI FAI UMJ - Nurmulia, Fatma; Farokhah , Laely; Lisdiyanti , Siti (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Mathematical literacy is an essential competency that must be possessed by prospective madrasah ibtidaiyah teachers in order to develop meaningful, contextual, and life-relevant mathematics learning, including Islamic values. This study aims to analyze the mathematical literacy skills of students in the Madrasah Ibtidaiyah Teacher Education Program (PGMI) at the Faculty of Islamic Studies, Muhammadiyah University Jakarta (FAI UMJ) in the context of Islam. The approach used is descriptive qualitative with data collection techniques in the form of mathematical literacy tests based on Islamic context, in-depth interviews, and document studies. The research subjects were purposively selected, consisting of sixth-semester students who have completed the Elementary School Mathematics and Islamic Religious Education courses. The research results show that students' mathematical literacy abilities are still in the moderate category, with the highest achievements in the indicators of mathematical communication and the use of representations, but low in the indicators of reasoning and problem-solving in an Islamic context. Most students are able to relate mathematical concepts to life phenomena in Islam, such as zakat, prayer times, and inheritance distribution, but still struggle to apply systematic problem-solving strategies. These findings indicate the need for a stronger integration between mathematics content and Islamic values in the PGMI curriculum, as well as the necessity for faculty training and the development of Islamic contextual learning media. This research contributes to the development of madrasah teacher education that not only masters mathematical concepts academically but is also able to internalize and teach them within the framework of Islamic values.